Education as a Catalyst for Social Justice: Exploring Ethical Dimensions in Curriculum Development and Implementation - Suprapti Suprapti (Education : Jurnal Sosial Humaniora dan Pendidikan, 2026)
Schooling is regularly positioned as a key instrument for advancing social justice; but, continual inequalities imply that curricula may additionally reproduce present power systems. This have a look at examines how ethical dimensions are embedded in curriculum development and implementation and their implications for social justice in training. A qualitative case examine technique grounded in crucial pedagogy became hired, concerning curriculum developers, instructors, and students decided on thru purposive sampling. data have been gathered via semi-based interviews, participatory observations, and document evaluation, and analyzed using critical thematic analysis with the aid of NVivo. The findings discover three critical issues: hegemonic hidden curriculum, trainer unpreparedness in addressing moral troubles, and the anxiety among standardization and social justice. The outcomes screen an opening between ethical intentions and lecture room practices, fashioned through bureaucratic pressures and evaluation regimes that constrain pedagogical flexibility. college students additionally showcase essential resistance in the direction of content material perceived as disconnected from their social realities. This have a look at contributes by means of linking curriculum design, pedagogical exercise, and scholar enjoy inside an moral framework, emphasizing the importance of ethical literacy in instructor It concludes that curriculum can only function as a catalyst for social justice whilst advanced via inclusive, dialogical, and significantly informed tactics.